PUTUSAN LEPAS DARI SEGALA TUNTUTAN HUKUM TERHADAP PELAKU KEKERASAN DALAM RUMAH TANGGA YANG MENYEBABKAN KEMATIAN (Studi Kasus Terhadap Putusan Perkara Nomor 16/ PID.B/2011/PN.BLK) - Ida Zulfamazidah (Jurnal Idea Hukum, 2017)
The application of criminal removal is a very important matter in the judgment. When consideration of improper judgment errors will obscure the essence of judicial and criminal law purposes. The purpose of this research is to analyze the application of criminal removal reasons based on Article 44 of the Criminal Code on judges' consideration in breaking free from all lawsuits against perpetrators of domestic violence that led to the death of Decision No. 16 / PID.B / 2011 / PN.BLK and also analyzing the suitability Consideration of the judge on the decision of the case with the purpose of criminal law.This research was conducted normatively and obtained the result that the Panel of Judges in breaking out of all lawsuits against perpetrators of domestic violence that led to death in the case Number 16 / PID.B / 2011 / PN.BLK using expert information that is psychiatrist as the only The basis for determining criminal responsibility or known by biological methods. Decision Number 16 / PID.B / 2011 / PN.BLK has been in accordance with the purpose of criminal law, one of which is achieved legal certainty, especially for the perpetrator.Â Key words : Decision, Out of all lawsuits, Article 44 of the Criminal Code.